1997
DOI: 10.1097/00002371-199707000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Infected with PoxvIn Vitro iruses Encoding MART-1/ Melan A Sensitize T Lymphocytes In Vitro

Abstract: Dendritic cells (DC) are potent professional antigen-presenting cells that can activate naive T lymphocytes and initiate cellular immune responses. As adjuvants, DC may be useful in enhancing the immunogenicity of tumor antigens and mediating tumor regression. Endogenous expression of antigen by DC offers the potential advantage of allowing prolonged constitutive presentation of endogenously processed epitopes and exploitation of multiple restriction elements for the presentation of the same antigen. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 58 publications
(74 reference statements)
0
42
0
Order By: Relevance
“…7,8,27 In particular, we observed that this strategy was more efficient than the exogenous pulsing of iDC with saturating levels of relevant epitope. 7,8 The reason for the enhanced efficiency remained unclear, and we postulated that the longer persistence of Ag on the surface of DC due to the prolonged production of antigenic molecules driven by the viral promoters might have been responsible. 8 Surprisingly, however, in the conduct of these studies we noted that rVV-infected DC had very little ability to stimulate generation of IFN-g production by several Agspecific T-cell clones studied (unpublished observation).…”
Section: Effect Of Rvv-gp100 Infection On the Phenotype Of Idc And MDCmentioning
confidence: 83%
See 4 more Smart Citations
“…7,8,27 In particular, we observed that this strategy was more efficient than the exogenous pulsing of iDC with saturating levels of relevant epitope. 7,8 The reason for the enhanced efficiency remained unclear, and we postulated that the longer persistence of Ag on the surface of DC due to the prolonged production of antigenic molecules driven by the viral promoters might have been responsible. 8 Surprisingly, however, in the conduct of these studies we noted that rVV-infected DC had very little ability to stimulate generation of IFN-g production by several Agspecific T-cell clones studied (unpublished observation).…”
Section: Effect Of Rvv-gp100 Infection On the Phenotype Of Idc And MDCmentioning
confidence: 83%
“…34 Indeed, we have utilized in the past rVV for the in vitro induction of antimelanoma differentiation antigen-specific CTL. 7,8 We, however, noted that MART-1/MelanA-specific immune reactivity was more easily elicited than that of the larger melanoma differentiation antigen gp100. In addition, we observed that the reactivity elicited against MART-1 was almost exclusively limited to the HLA-A*0201-associated MART-1:27-35 epitope, suggesting that the immunogenicity of a protein may not be necessarily expandable to multiple HLA alleles as desired by the whole Ag vaccination approach.…”
Section: Epitope Selection In Vaccinia-virus-infected Dendritic Cellsmentioning
confidence: 93%
See 3 more Smart Citations